Bio-macromolecular dynamic structures and functions, illustrated with DNA, antibody, and lipoprotein - 缑璐;金桃丽;陈淑玉;李娜;郝东晓;张胜利;张磊 (Chinese physics B, 2018)
Bio-macromolecules, such as proteins and nucleic acids, are the basic materials that perform fundamental activities required for life. Their structural heterogeneities and dynamic personalities are vital to understand the underlying functional mechanisms of bio-macromolecules. With the rapid development of advanced technologies such as single-molecule tech- nologies and cryo-electron microscopy （cryo-EM）, an increasing number of their structural details and mechanics properties at molecular level have significantly raised awareness of basic life processes. In this review, firstly the basic principles of single-molecule method and cryo-EM are summarized, to shine a light on the development in these fields. Secondly, recent progress driven by the above two methods are underway to explore the dynamic structures and functions of DNA, antibody, and lipoprotein. Finally, an outlook is provided for the further research on both the dynamic structures and functions of bio-macromolecules, through single-molecule method and cryo-EM combining with molecular dynamics simulations.